PENGARUH EFIKASI DIRI TERHADAP KESIAPAN KERJA MELALUI EMPLOYABILITY SKILLS PADA SISWA KELAS XII MPLB SMK PGRI 2 KEDIRI - Safitri, Rahmadani Dinda Nur; Puspasari, Durinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocational High Schools (SMK) continue to experience the highest unemployment rate among all educational levels in Indonesia. According to tracer study data from the Office Management and Business Services (MPLB) Program at SMK PGRI 2 Kediri, 36.6% of graduates were still searching for employment after graduation, indicating that students' work readiness remains insufficient. This study was conducted to examine the influence of self-efficacy on work readiness, with Employability skills serving as a mediating variable. A quantitative approach with an explanatory research design was employed using path analysis. The research involved 82 twelfth-grade MPLB students selected through proportional random sampling. Data were collected using online questionnaires, analyzed with SPSS version 26, and the mediating effect was evaluated through the Sobel test. The results demonstrated that self-efficacy significantly and positively influenced Employability skills (β = 0,681; p < 0,000) as well as work readiness (β = 0,270; p < 0,024). In addition, Employability skills showed a significant positive effect on work readiness (β = 0.431; p < 0.000). The Sobel test yielded a statistical value of 3.384, confirming that Employability skills significantly mediated the relationship between self-efficacy and work readiness. Furthermore, the indirect effect (0.293) exceeded the direct effect (0.270), indicating that stronger Employability skills enhance the contribution of self-efficacy to students work readiness. These findings highlight the importance of strengthening both students self-efficacy and Employability skills to improve their preparedness for entering the workforce.